Roles of Municipal Councils in Poland and in the Czech Republic: Factors Shaping the Roles and the Dynamic of Change (Journal of Universal Excellence, 2026)
Research Question (RQ): After many years of not being in vogue, the issue of representative democracy at the local level has yet again caught the scholars’ attention. The interest is related both to falling turnout in local elections, disappointment in party politics as well as to the impact of the new trends such as the strengthening of the executive power or citizens’ more direct involvement in the decision-making process. Quite often the afore-mentioned trends force local councils to redefine their roles.Purpose: The main objective of the article is to investigate the factors that shape the roles of municipal councils in two CEE countries, Poland and the Czech Republic, and to track the possible dynamic of their change.Method: The analysis conducted in the paper is grounded mainly in institutional theory. The study is based on available statistic data, examination of legal regulations, documents and information included in the corpus of selected articles and books.Results: The outcome of the analysis conducted indicates that in both countries the basic roles of councils – representative, decision-making and administrative one – are being diminished. Nevertheless, the existing institutional framework as well as reforms implemented in recent years provide potential for the development of new roles, such as the facilitator of the governing process or a network coordinator.Organization: The paper may contribute to better organisation of local administration at the municipal level.Society: The study has an impact on the understanding of representative democracy in local self-governments.Originality: The paper elaborates on representative democracy at the municipal level in Poland and the Czech Republic, countries where the discussion over this issue is still much less visible than in Western Europe.Limitations / further research: The paper should be mainly perceived as a kind of theoretical introduction to further empirical research into the changing roles of municipal councils in Central and Eastern European countries.
Keywords: municipal councils; Poland; the Czech Republic; role; local democracy; governance